IMPLEMENTASI KONSEP KEADILAN DENGAN SISTEM NEGATIF WETTELIJK DAN ASAS KEBEBASAN HAKIM DALAM MEMUTUS SUATU PERKARA PIDANA DITINJAU DARI PASAL 1 UNDANG-UNDANG NO 4 TAHUN 2004 TENTANG KEKUASAAN KEHAKIMAN (Analisa putusan No.1054/Pid.B/2018/PN.Jkt.Sel ) - Eldo Pranoto Putra; Muhamad Iqbal (Rechtsregel : Jurnal Ilmu Hukum, 2020)
An independent judicial power is one of the characteristics of a democratic state, no country can be called a democratic state without the practice of an independent judicial power. However, there are negative comments and views on judges regarding the extent to which judges can work objectively, and whether it is impossible that judges who are constructed as free and impartial human beings will not be "biased" in examining and deciding the cases they face, this study aims to know the extent to which a judge uses his freedom and confidence in deciding a criminal case